The influence of coping strategies on resilience among undergraduate students: The mediating role of trait mindfulness - Chaturapanich, Traipop (Humanities, Arts and Social Sciences Studies, 2023)
Mindfulness helps people increase resilience and cope with stress, serving as a mediating variable between stress and mental well-being. Does mindfulness also improve the effectiveness of coping strategies? What strategies could influence resilience through mindfulness? This research revealed that trait mindfulness also plays an important role in mediating the influence of coping strategies on individual resilience. Online questionnaires were used to collect data from 221 undergraduate students between the ages of 18 and 23. The survey comprised three optimized scales: the coping strategies scale consisted of three categories, the mindfulness scale, and the resilience scale. Mediation regression analysis was used to analyze the data. This study shows that the use of several coping strategies enhances an individual’s resilience through the facilitation of trait mindfulness. Active (taking steps to deal with a problem) and positive reinterpretation have the greatest indirect effects on resilience (b = 0.19), followed by planning (finding solutions deliberately) (b = 0.18), suppression (minimizing irrelevant matters) (b = 0.17), acceptance (accepting the problem honestly), and denial (denying the existence of a problem) (b = 0.14), respectively. The strategies that have lower indirect effects are restraint (waiting for an appropriate moment) (b = 0.09) and mental disengagement (diverting attention away from a problem) (b = 0.06). Additionally, a partial indirect effect was found in humor (changing one’s perspective on the situation to a humorous one). It is noted that these strategies are all related to mind control; thus, it is possible that mindfulness promotes more effective regulation of the thoughts underlying these strategies. Therefore, dispositional mindfulness formation in youth should be encouraged to promote their ability to cope with difficulties. However, a qualitative approach is needed for further research.